DGS Based CP Antenna for 5G Communication with Harmonic - Misran, Mohamad Harris; Meor Said, Maizatul Alice; Othman, Mohd Azlishah; Jaafar, Abd Shukur; Abd Manap, Redzuan; Suhaimi, Shadia; Hassan, Nurmala Irdawaty (International Journal of Integrated Engineering, 2024)
Higher harmonics in antennas contribute to negative effects on antenna performance such as interference, radiation pattern distortion, impedance mismatch and increased complexity in design, commonly occurring in RF communication systems caused by the non-uniformity of the antenna structure and the presence of parasitic elements. Therefore, a patch antenna operating at 3.65GHz for 5G mobile communication that incorporates techniques to suppress unwanted higher harmonics is presented. The antenna design employs a basic rectangular patch antenna with an inset feed technique to enhance the S11 parameters at the resonant frequency. Additionally, two dumbbell defected ground structures (DGS) are employed to minimize the higher modes of harmonic distortion. To transform the antenna into a circular polarized (CP) antenna, two truncated corners and a cross slot perpendicular to the middle of the patch are introduced. The proposed antenna is able to suppress unwanted harmonics at higher resonances, demonstrating its effectiveness in mitigating harmonic distortion.